Arterial Stiffness Is Related to Systemic Inflammation in Essential Hypertension - Mahmud, Azra; Feely, John (Hypertension (Dallas, Tex. 1979), 2005)
The acute phase–reactant high-sensitivity C-reactive protein, a marker of vascular inflammation and an atherosclerotic risk factor, is related to arterial stiffness in healthy subjects and in systemic vasculitis. To explore the relationship between markers of inflammation, interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and high-sensitivity C-reactive protein with arterial stiffness, we studied untreated patients (n=78; 56% male; 47±1 years of age; mean±SEM) with essential hypertension. After overnight fast, augmentation index and pulse wave velocity were assessed noninvasively and related to plasma levels of inflammatory markers measured by ELISA. Pulse wave velocity was significantly related to plasma high-sensitivity C-reactive protein (r=0.31; P<0.001), TNF-α, (r=0.30; P<0.001) and IL-6 (r=0.21; P<0.05). There was also a relationship between heart rate–corrected augmentation index to high-sensitivity C-reactive protein (r=0.37; P<0.001), IL-6 (r=0.24; P<0.05), and TNF-α (r=0.19, P=0.06). High-sensitivity C-reactive protein was an independent predictor of pulse wave velocity and augmentation index in a multiple stepwise regression model. High-sensitivity C-reactive protein, a marker of systemic inflammation, is independently related to pulse wave velocity, a marker of aortic stiffness, and augmentation index, a manifestation of wave reflection, in essential hypertension.